Enhancing resilience in South African small and medium enterprises: a dynamic capabilities perspective - Matikiti, Edmore (Graduate School of Business (GSB), 2025)
The resilience of small and medium-sized enterprises (SMEs) in emerging markets, where they confront persistent institutional challenges, is crucial for their ability to survive and thrive in such complex environments. South Africa contends with many challenges, including institutional voids that manifest in various ways, such as electricity blackouts and systemic corruption. These challenges compound the existing difficulties SMEs face, which are already constrained by limited resources. The emergence of the COVID-19 pandemic, as an exogenous shock, exacerbated the challenges small enterprises face. It further heightened transaction costs, introduced additional operational constraints, and underscored the urgency of examining their resilience. The aim of the study is to understand how market dynamism in the form of institutional voids and exogenous shocks influences SME resilience in emerging markets. Additionally, the study investigates the role of the dynamic capabilities framework to deepen comprehension of organizational resilience within these markets. Targeting South African SMEs across diverse sectors with fewer than 250 employees and annual revenue below R220 million, the research employed a mixed methods approach combining case studies and a survey to gather data. The study confirms significant relationships between institutional voids, exogenous shocks, dynamic capabilities, and SME resilience using qualitative and quantitative analysis methods, including regression analysis and structural equation modelling. To survive and thrive, South African SMEs must develop and deploy context-specific and distinctive resilience capabilities to navigate these disruptions and challenges proficiently. Specifically, the study's findings highlight that tacit and explicit knowledge and improvisation capability positively impact SME resilience, enabling these enterprises to mitigate risks and identify opportunities, thereby fortifying their resilience during crises. This thesis contributes to existing theory by introducing a Resilience Framework, depicting essential categories and specific qualities crucial for managing disruptions and enhancing SME resilience within emerging markets. Furthermore, the study offers theoretical advancements in dynamic capabilities and resilience and furnishes practical strategies for SME managers and policymakers. This approach serves as guidance for current decision-making and lays the groundwork for future research endeavors in these domains.